1954
DOI: 10.1017/s0021859600044774
|View full text |Cite
|
Sign up to set email alerts
|

The influence of time, temperature, pH and calcium carbonate on the activity of the phytase of certain cereals

Abstract: 1. Tests have been carried out to investigate the hydrolysis of phytate in wheat, bran, and oats.2. Oats showed practically no phytase activity.3. Wheat phytase had an optimum pH of 5·0–5·1 and functioned at pH values down to 3·0. When hydrolysis had been arrested by acidifying to pH 2·5 for 5 min. or longer, the phytase did not recover when the pH was raised to 5·0 by the addition of sodium bicarbonate.4. There was an almost uniform increase in the rate of hydrolysis between 15 and 50° C.5. The rate of phytat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1961
1961
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Calcium-phytate complexes and phytase activity Ballam et al (1985) stressed the importance of Ca and Caphytate complexes on phytate degradation and the liberation of phytate-P. In support of this, Hill and Tyler (1954a) found that Ca reduced phytate hydrolysis by wheat phytase by 22% in an in vitro system. Also, Gillis et al (1957) reported that radioactively-labeled Ca-phytate bioavailability was negligible in comparison to inorganic P (Na 2 HP 32 O 4 ) as assessed by P retention in tibia ash of broiler chicks and turkey poults.…”
Section: Feed Ingredientmentioning
confidence: 84%
See 1 more Smart Citation
“…Calcium-phytate complexes and phytase activity Ballam et al (1985) stressed the importance of Ca and Caphytate complexes on phytate degradation and the liberation of phytate-P. In support of this, Hill and Tyler (1954a) found that Ca reduced phytate hydrolysis by wheat phytase by 22% in an in vitro system. Also, Gillis et al (1957) reported that radioactively-labeled Ca-phytate bioavailability was negligible in comparison to inorganic P (Na 2 HP 32 O 4 ) as assessed by P retention in tibia ash of broiler chicks and turkey poults.…”
Section: Feed Ingredientmentioning
confidence: 84%
“…Decades ago, Hill and Tyler (1954a) reported that Ca reduced wheat phytase efficacy, which was attributed Caphytate complex formation. Subsequently, Lei et al (1994) reported that Ca, and/or 'wide' dietary Ca:P ratios, depressed responses to exogenous phytase in weaner pigs, which was also attributed to phytate complexing Ca.…”
Section: Introductionmentioning
confidence: 99%
“…The pH optimum of both phytases is about 5.5. With decreasing pH, plant phytase activities are extremely low, 25,26 whereas microbial phytase still exhibits 60% of its original activity at pH 2.0. 27,28 Thus it can be assumed that microbial phytase is still active in the fundic region of the stomach of the pig.…”
Section: Discussionmentioning
confidence: 99%
“…1997) resulting in a higher inactivation by a delayed transit of the enzyme through the stomach. Low pH values and the presence of pepsin caused significant losses of wheat phytase activity (H ILL and T YLER 1954; N AGAI and F UNAHASHI 1962; S CHEUERMANN et al. 1988).…”
Section: Discussionmentioning
confidence: 99%